(untitled) (Indian Journal of Public Health Research & Development, 2022)
Background: The bulk of oxygen in blood is normally transported as oxyhemoglobin. The amount of oxyhemoglobin is often expressed as percentage saturation (Spo2). Objective: Oxygen saturation is one of the vitals monitored in clinical practice and also the most important vital monitored in COVID-19patients since it’s the oxygen saturation which gets depleted in these patients. COVID pandemic has taken heavy toll on health and life of the people and since different people respond to COVID-19 differently so the response is multifactorial. The exposure to lower oxygen levels may have important clinical consequences, particularly in physiologic processes like respiratory drive, which are dependent on PO2 in the blood. Hence our aim is to study the effect of BMI and Hb on oxygen saturation (SPO2). Method: A descriptive cross-sectional study was conducted in Department of Physiology, SKIMS-Medical College. Data was collected by using self-administered questionnaire followed by anthropometric measurement. Body Mass Index (BMI) by Quetelet’s index and Haemoglobin (Hb) concentrations by Sahli’s method were assessed. Pulse oximetry was done to know the oxygen saturation. Results: The students with high BMI show negative correlation with oxygen saturation while as Hb with oxygen saturation shows positive correlation. These results have important clinical implications while treating patients with high BMI or low Hb